عملية تعليم اللغة العربية في المدرسة العالية الإسلامية الأهليّة بادنج غنتينج - Ardila Iswanda; Devy Aisyah (Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
مستخلص البحث: الغرض من هذا البحث لوصفية عن مادة تعليم، وطريقة تعليم، ووسيلة تعليم، وتقويم تعليم، ومشكلة تعليم اللغة العربية في المدرسة العالية الإسلامية الأهليّة بادنج غنتينج. هذا البحث يستعمل المدخل الكيفي بمنهج دراسة حالة. وأما طريقة جمع البيانات هي الملاحظة والمقابلة والوثائق. و أما تصحيح البيانات بتثليث طريقة. نتائج هذا البحث فيما يأتي: مادة تعليم اللغة العربية مأخوذة من كتاب اللغة العربية على قرار وزارة الشؤون الدينية رقم 183 لعام 2019 والتي تتكون من مهارة الاستماع، والكلام، والقراءة، والكتابة وقواعد. طريقة تعليم هي طريقة القواعد والترجمة، وطريقة القراءة، وطريقة المباشرة، وطريقة الإملاء. وأما وسيلة تعليم سبورات، وأقلام الحبر، وكتب اللغة العربية، وممسحة، وصورات، والأشياء المحيط. تقويم تعليم اختبار الإملاء، واختبار قراءة النص وترجمته، والحوار أو التحدث مباشرة إلى المدرس باللغة العربية، واختبار القواعد هو تحديد موضع كلمة من الجملة أو إعطاء حركات في الجملة. مشكلات تعليم اللغة العربية يعني بعضهم عدم إتقان المفردات للطلاب، بعضهم لا يقرأ الطلاب النص العربي بشكل صحيح لأنهم لا يجيدون قراءة القرآن، وأحيانا مادة تعليم اللغة العربية صعوبة على الطلاب، ونقص الكتب العربية ووسائل التعليم الأخرى لمساعدة عملية تعليم اللغة العربية. Abstract The purpose of this study was to describe learning materials, learning methods, learning media, learning evaluations, and obstacles to learning Arabic at MAS Plus Padang Ganting. This research uses a qualitative approach with a case study method. Data collection methods are observation, interviews and documentation. The technique of guaranteeing the validity of the data is by using source triangulation, method triangulation, and discussion . The Arabic language teaching material is taken from the Arabic language book on the decision of the Ministry of Religious Affairs No. 183 of 2019, which consists of the skill of listening, speaking, reading, writing and grammar. The learning methods used are grammar and translation methods, reading methods, directness methods, and dictation methods. The learning media are blackboards, ink pens, Arabic books, erasers, pictures, and objects around them. The evaluation of Arabic learning is a dictation test, a text reading and translation test, dialogue or speaking directly with a teacher in Arabic, and a grammar test by determining the position of words in sentences or giving lines in sentences. Obstacles in teaching Arabic, namely some students lack vocabulary mastery, some students do not read Arabic texts properly because they are not good at reading the Qur'an, and sometimes Arabic material is difficult for students to understand, and the lack of Arabic books and other learning media to assist the process of teaching Arabic.